2005
DOI: 10.1308/1478708051667
|View full text |Cite
|
Sign up to set email alerts
|

Day-case breast cancer axillary surgery

Abstract: 96Ann R Coll Surg Engl 2005; 87 B reast cancer is the commonest malignancy in women 1 with 29,000 new cases per year being diagnosed in England and Wales. The aggressive approach with radical surgery has changed over the years to being more conservative.2 Standard treatment for most women, now, is excision of the primary tumour (by wide local excision or mastectomy) with axillary lymphadenectomy. This permits locoregional control, staging and accurate prognostication. Suction drainage of the axilla is stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
(5 reference statements)
1
15
0
3
Order By: Relevance
“…Besides hernia repairs, many other surgical procedures can be achieved on a day-case setting [20][21][22]. The mean discharge time was 122 min in the present series.…”
Section: Discussionmentioning
confidence: 71%
“…Besides hernia repairs, many other surgical procedures can be achieved on a day-case setting [20][21][22]. The mean discharge time was 122 min in the present series.…”
Section: Discussionmentioning
confidence: 71%
“…As the infrastructure of ambulatory surgery improved, other interventions came to the new day surgery units. New upcoming interventions, among others, are laparoscopic cholecystectomy and Nissen fundoplication, minimally invasive parathyroidectomy, axillary dissection, and laparoscopic adrenalectomy, for which several studies have shown the safety and feasibility [1,4,6,[9][10][11][12][13]. Morbidly obese patients are a distinct patient category with their own surgical and anesthesiologic challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Teams practicing ambulatory surgery have shown that there are benefits for the patients [7][8][9]. Encouraged by our administration, we were able to perform ambulatory breast surgery in spite of the financial penalty.…”
Section: %mentioning
confidence: 99%
“…Rather than extend the indications, it seems preferable to us that the French hospital centers concentrate on ambulatory senologic surgery. Conservative senologic surgery can be accomplished in the ambulatory setting [6][7][8]. This is what should be promoted.…”
Section: %mentioning
confidence: 99%